2016
DOI: 10.1002/clen.201300853
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Phenolic Compounds in Palm Oil Mill Effluent by Silica‐Immobilized Bacteria in Internal Loop Airlift Bioreactors

Abstract: Palm oil mill effluent (POME) is usually treated using biological systems. However, phenolic compounds remain in the treated POME. This study aimed to remove phenolic compounds from POME using silica‐immobilized Methylobacterium sp. NP3 and Acinetobacter sp. PK1. Treated POME samples were collected from the final stabilization ponds of two palm oil mills in Thailand. In batch experiments, the silica‐immobilized bacteria effectively degraded 100–500 mg/L phenolic compounds (e.g., caffeic acid, ferulic acid, 4‐h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Using Acinetobacter sp. PK1, phenolic compounds including FA and PHBA are removed from palm oil mill effluent ( Khongkhaem et al, 2016 ). To the best of our knowledge, it has not been reported that strains of Acinetobacter might degrade a mixture of FA and PHBA in soil.…”
Section: Introductionmentioning
confidence: 99%
“…Using Acinetobacter sp. PK1, phenolic compounds including FA and PHBA are removed from palm oil mill effluent ( Khongkhaem et al, 2016 ). To the best of our knowledge, it has not been reported that strains of Acinetobacter might degrade a mixture of FA and PHBA in soil.…”
Section: Introductionmentioning
confidence: 99%
“…POME is considered a harmful pollutant to the aquatic environment since it uses the available oxygen in the river for degradation process. This phenomenon leads to depletion of available oxygen for the existing aquatic lives in the water [5]. Therefore, treatment process is required before discharging to waterways.…”
Section: Pome and Pollutionmentioning
confidence: 99%
“…NP3 and Acinetobacter sp. PK1 [2,27] or fungi such as Trametes hirsuta AK04 [3] and Pleurotus sajor caju [28] in the grass-soil pots to support the activity of soil bacteria.…”
Section: Comparison Of Various Grasses On Reducing Phenolic Compoundsmentioning
confidence: 99%
“…The effluent from stabilization ponds or treated POME (TPOME) has better water quality but still contains toxic phenolic compounds. Recently, several bacterial and fungal strains have been found to degrade up to 80-90% of 27-475 mg/L phenolic compounds in TPOME [2][3][4]. These microbial strains usually applied as immobilized cells in bioreactor with aeration unit, thus the process construction and operation will be inconvenient and costly.…”
Section: Introductionmentioning
confidence: 99%